2014
DOI: 10.2174/1389202915666140528003249
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Review of Dysregulated miRNAs Involved in Cervical Cancer

Abstract: MicroRNAs(miRNAs) have become the center of interest in oncology. In recent years, various studies have demonstrated that miRNAs regulate gene expression by influencing important regulatory genes and thus are responsible for causing cervical cancer. Cervical cancer being the third most diagnosed cancer among the females worldwide, is the fourth leading cause of cancer related mortality. Prophylactic human papillomavirus (HPV) vaccines and new HPV screening tests, combined with traditional Pap test screening ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 162 publications
(164 reference statements)
1
46
0
1
Order By: Relevance
“…MiRNAs, a subset of short noncoding RNAs (17–22 nucleotides), could post‐transcriptionally regulate the expression of relevant genes and thus participate in the development of cervical cancer . Approximately, 70 miRNAs have been discovered to be involved in cervical cancer thus far and the list is ever growing .…”
Section: Introductionmentioning
confidence: 99%
“…MiRNAs, a subset of short noncoding RNAs (17–22 nucleotides), could post‐transcriptionally regulate the expression of relevant genes and thus participate in the development of cervical cancer . Approximately, 70 miRNAs have been discovered to be involved in cervical cancer thus far and the list is ever growing .…”
Section: Introductionmentioning
confidence: 99%
“…Cervical cancer is one of the most common types of gynecologic cancer, and is the fourth leading cause of cancer-associated mortality among females worldwide (14). Previous studies have demonstrated that miRNAs may be abnormally expressed in cervical cancer and this is associated with the prognosis of cervical cancer (15,16). Zhao et al (17) validated that the expression level of miR-491-5p was significantly decreased in cervical cancer and that miR-491-5p inhibited cancer cell proliferation, primarily by regulating human telomerase reverse transcriptase.…”
Section: Mir-494 Expression Is Decreased In Cervical Cancermentioning
confidence: 99%
“…miR-21 a miR-146a [13,16]. Pro definitivní validaci vybraných miRNA bude ovšem potřeba provést více nezávislých studií a rovněž popsat přesnou roli jednotlivých miRNA v karcinogenezi indukované virem HPV.…”
Section: Genom Hpv 16unclassified